Adjustment of sperm cryopreservation laboratory management during the COVID-19 pandemic - Dicky Moch Rizal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The COVID-19 pandemic has changed the order of life in all fields, particularlyin medical services. Laboratory services in sperm cryopreservation that partof andrology or in vitro fertilization (IVF) laboratory cannot be separated withhandling sperm from patients. Although the presence of viruses in semenhas been known through various studies, there is scarce evidence regardingwhether sperm fluid can be a medium of COVID-19 transmission. This raisedthe question of whether some adjustments to manage patient sperm shouldbe made. This review described an overview of the various efforts that can bemade to reduce the risk of disease transmission to health workers who handlepatient sperm fluid.